Evaluation of damage induced in graphite due to sample preparation by standard non-destructive techniques - Lasithiotakis, M; Marrow, JT; Marsden, BJ (Peter the Great St Petersburg Polytechnic University; Institute of Problems of Mechanical Engineering, Russian Academy of Sciences, 2020)
Damage introduced to graphite by mechanical polishing, argon ion beam polishing, fracture, and neutron bombardment has been studied in polycrystalline graphites and Highly Oriented Pyrolytic Graphite (HOPG). Scanning Electron Microscopy and Atomic Force Microscopy, as well as X-Ray Diffraction and Raman spectroscopy, were employed. The least disturbed surfaces are observed in pristine HOPG or by fracturing techniques that exposed pre-existing defects. A decrease of the mean particle size of the abrading medium and the use of ions and neutrons increased the D band and decreased the pseudo–crystallinity.